Efektivitas Penerapan LKPD Berbasis Problem-Based Learning pada Mata Pelajaran Dasar-dasar Teknik Ketenagalistrikan - Alwi Fermana Hakim; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The purpose of this study was to reveal the effectiveness of the application of problem-based learning-based LKPD on the learning outcomes of students in class X TKL in the subject of Electrical Engineering Basics at SMKN 1 Bukittinggi. The effectiveness was tested to determine the effectiveness of implementing problem-based learning worksheets on student learning outcomes. This type of research is experimental research using one group pretest-posttest design. This research was conducted at SMKN 1 Bukittinggi in class X TKL totaling 34 students. The research instrument used was a test of learning outcomes in the form of multiple choice questions, consisting of a pretest (pretest) and a final test (posttest). The results of data analysis showed that the percentage of classical completeness at the pretest was 41.1% and the posttest was 88.2%, meaning that the application of the LKPD was effectively used. This is also supported by the t-test, obtained a significance value, meaning that there is an increase in learning outcomes between the use of before and after using LKPD. Based on the effect size test, it shows that there is an impact in increasing learning outcomes of 1.23 which is categorized as large. So, it can be concluded that the application of problem-based learning-based LKPD before and after using the LKPD is declared to be effectively applied in learning the Basics of Electrical Engineering subjects.